Preparation method of multicomponent alloy ultra-black powder with diatom shell structure
By depositing, etching and filling metal ions on the diatom shell structure, a multi-alloy ultra-black powder with high absorbance was prepared, which solved the problem of light absorption reduction caused by structural unevenness in the prior art, and achieved the performance improvement of ultra-black powder in multiple fields.
Patent Information
- Application Number
- CN202411802860.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The existing ultra-black powder preparation technology has the problem of structural unevenness, which leads to a decrease in light absorption, limiting its application in optical instruments, aerospace and military fields.
The preparation method of multi-alloy ultra-black powder with a diatom shell structure is adopted to achieve densification and transformation of the structure by depositing a variety of metal ions, etching and removing amorphous silica, and filling pores.
The absorption rate of ultra-black powder to light at wavelengths of 180 nanometers to 3000 nanometers is significantly improved, especially in the visible light area, which greatly improves its optical performance.
Smart Images

Figure CN119609120A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of new materials, and in particular to a method for preparing a multi-component alloy ultra-black powder with a diatom frustule structure. Background Art
[0002] Ultra-black powder usually refers to a powdery substance that has a strong ability to absorb light, has a very low reflectivity in the visible spectrum, and looks almost black. Its most notable feature is that it can absorb incident light to the maximum extent, converting most of the light energy into other forms of energy such as heat, and reflects very little light. Often, its reflectivity can be as low as a few tenths of a percent or even lower, giving people a visual sense of "bottomless" extreme black.
[0003] Due to its special properties, super black powder has extensive and important applications in a variety of modern industries and scientific fields such as optical instruments and equipment, aerospace, and military fields. For example, in optical telescopes, microscopes and other equipment, super black powder can be used to make extinction components, reduce the impact of stray light, and improve the imaging quality and resolution of the instrument. For example, coating the surface of the internal structure of an astronomical telescope with super black powder can effectively absorb scattered light and make the observed celestial body image clearer. For example, using super black powder on the surface of some light-sensitive detectors of spacecraft can reduce reflectivity, help improve the sensitivity of the detector to the target signal, and also use its light absorption to convert into heat to assist in heat management. Super black powder can absorb visible light and part of infrared light, so that military equipment can achieve stealth effect to a certain extent and reduce the probability of being discovered by the enemy.
[0004] Existing ultra-black powder preparation technologies usually include chemical vapor deposition, physical vapor deposition and sol-gel method. These technologies usually have the problem of uneven structure of the obtained powder products, resulting in a decrease in the powder absorbance due to the uniformity of the structure, thus limiting the promotion and application of ultra-black powder.
[0005] Therefore, it is necessary to propose a new preparation method to solve the above problems and obtain ultra-black powder with high absorbance. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing multi-element alloy ultra-black powder with diatom frustule structure.
[0007] To solve the technical problem, the solution of the present invention is:
[0008] Provided is a method for preparing a multi-element alloy ultra-black powder having a diatom frustule structure, comprising the following steps:
[0009] (1) According to the molar ratio of Ce: Co: Cu: La: Ni: Zn: Ag being 0.05: 0.1: 0.1: 0.9: 0.9: 1.0: 25, the corresponding metal salt is taken as the solute; glycerol, sorbitol, and deionized water are taken at a mass ratio of 1: 1: 4, mixed evenly, and used as the solvent; the solute is added to the solvent, stirred until completely dissolved to obtain a solution 1;
[0010] (2) adding disodium ethylenediaminetetraacetate and sodium citrate to solution 1 in a molar ratio of total metal salts: disodium ethylenediaminetetraacetate: sodium citrate of 1:1:2, and stirring until completely dissolved to obtain solution 2;
[0011] (3) adding diatomaceous earth to solution 2 at a mass ratio of diatomaceous earth to solution 2 of 3:7, and continuously stirring for 24 to 72 hours to obtain a mixed solution 1;
[0012] (4) adding the mixed solution 1 to a hydrothermal kettle with stirring, and starting stirring first; after sealing the hydrothermal kettle, stepwise heating to 200° C. under stirring, and keeping the temperature for 10 to 12 hours; stopping heating and cooling to room temperature to obtain a mixed solution 1;
[0013] (5) taking out the mixture 1, filtering it, washing it with deionized water, and drying it to obtain a powder 1;
[0014] (6) adding powder 1 to a mixed solution containing KOH and CsOH; heating to 65° C. under stirring conditions, and keeping the temperature for 8 to 12 hours; stopping heating and cooling to room temperature, filtering and washing with deionized water, and drying to obtain powder 2;
[0015] (7) Repeat steps (1) and (2) to obtain solution 3; add powder 2 to solution 3 at a mass ratio of 2:8, and continue stirring for 10 to 30 minutes to obtain mixed solution 2;
[0016] (8) Adding the second mixed solution into a hydrothermal kettle with stirring, and starting stirring first; after sealing the hydrothermal kettle, stepwise heating to 220° C. under stirring, and keeping the temperature for 10 to 12 hours; stopping heating and cooling to room temperature to obtain the second mixed solution;
[0017] (9) taking out the mixture 2, filtering it, washing it with deionized water, and drying it to obtain a powder 3;
[0018] (10) adding powder 3 into a sodium borohydride aqueous solution, heating to 65° C., and stirring continuously for 3 to 5 hours; cooling to room temperature, filtering, and washing with deionized water to obtain powder 4;
[0019] (11) The powder is placed in a tube furnace, and a mixture of 75% hydrogen and 25% nitrogen is introduced. After burning, the powder is naturally cooled to room temperature to obtain a multi-element alloy powder with a diatom frustule structure.
[0020] As a preferred embodiment of the present invention, in step (1), the metal salt is Ce(NO3)3, Co(NO3)2, Cu(NO3)2, La(NO3)3, Ni(NO3)2, Zn(NO3)2 and AgNO3.
[0021] As a preferred embodiment of the present invention, in step (1), the mass ratio of the total mass of the solute to the mass of the solvent is 30%.
[0022] As a preferred embodiment of the present invention, in the step (4), the mixed solution is stirred for 10 to 20 minutes at a stirring rate of 300 rpm before the hydrothermal kettle is sealed; after the hydrothermal kettle is sealed, the stirring condition is maintained; the temperature is first raised to 95°C and kept warm for 1 to 3 hours; then the temperature is raised to 185°C and kept warm for 2 to 4 hours; and then the temperature is raised to 200°C and kept warm for 10 to 12 hours.
[0023] As a preferred embodiment of the present invention, in steps (5), (6), (9) and (10), the filtrate is filtered and then washed three times with deionized water.
[0024] As a preferred embodiment of the present invention, in step (6), the concentration of the mixed solution of KOH and CsOH is 2 mol / L, the molar ratio of KOH to CsOH in the solution is 3:1; and the stirring rate is 300 rpm.
[0025] As a preferred embodiment of the present invention, in the step (8), before the hydrothermal kettle is sealed, the mixed solution 2 is stirred for 10 to 20 minutes at a stirring rate of 300 rpm; after the hydrothermal kettle is sealed, the stirring condition is maintained; the temperature is first raised to 110° C. and kept warm for 1 to 3 hours; then the temperature is raised to 165° C. and kept warm for 2 to 4 hours; and then the temperature is raised to 220° C. and kept warm for 10 to 12 hours.
[0026] As a preferred embodiment of the present invention, in step (10), the mass percentage concentration of the sodium borohydride aqueous solution is 25 wt%.
[0027] As a preferred embodiment of the present invention, in the step (10), the calcination refers to heating the powder to 750° C. and keeping the temperature for 10 to 12 hours.
[0028] Description of the invention principle:
[0029] Diatomite is mainly composed of diatom shells, which have a fine and complex microstructure. There are a large number of pores, grooves and textures of different shapes on its surface, which constitute a rich microporous structure with a porosity of 60%-80%. These micropores vary in size, ranging from a few nanometers to hundreds of nanometers, and the pores are orderly or regularly distributed, forming a periodic porous structure. During the in-depth research, the applicant noticed that the size of these microstructures is usually at the nanometer to micrometer level, which is similar to the wavelength of visible light and infrared light. This lays a structural foundation for its special effect on light and its role as a light trap.
[0030] The present invention innovatively proposes that, first, a plurality of metal ions are deposited on the surface of the diatom shell in the form of a complex to form a deposition layer, and then the amorphous silica in the diatom shell is removed by an etching process; and then the pores left after the silica removal are filled by repeated deposition to complete the densification and enhancement of the diatom shell structure. The present invention is based on the technical transformation of deposition, etching and filling of the original structure of the diatom shell, retaining the unique porous optical structure of the diatom shell, the porous structure can increase the scattering and absorption path of light, so that the light is reflected and refracted multiple times inside the powder, thereby greatly improving the light absorption efficiency, and at the same time using the intrinsic electronic structure of the multi-component alloy to achieve high light absorption: (1) The photonic band gap generated by the periodic porous structure can induce the enhancement of light absorption and light reflection; (2) The multi-level channel structure can enhance light scattering, increase the propagation path length of light in the diatom shell, and increase the probability of interaction between light and matter; (3) The deposition structure of multiple metal components can further enhance the absorption and scattering effect of light, which helps to enhance the light absorption performance of the ultra-black powder and make its color darker.
[0031] The present invention uses a specific multi-element alloy component as a component of the monomer skeleton in the product. The atomic interaction in the alloy will change the mean free path of electrons, the electron state density, etc., so that the interaction between the movement of electrons and light changes. On the one hand, alloying can change the difficulty of electrons in transitioning between energy bands and increase the probability of light absorption; on the other hand, it will affect the mode of collective oscillation of electrons, increase the damping of oscillations, aggravate energy loss, thereby increasing the imaginary part of the refractive index and forming a high absorption of light. In addition, the microporous structure of the diatom shell structure forms a large number of high curvature sites inside the powder, thereby affecting the distribution density of electrons. In areas with large curvature, the binding force on electrons is relatively weak, and the electron cloud will tend to gather in these areas, resulting in an increase in local electron density, which in turn leads to an increase in plasma frequency, so that the metal powder has strong absorption in a wider spectral range.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention creatively utilizes the optical properties of the original structure of diatom shells, and further realizes structural transformation through etching and filling after deposition of metal complexes. The obtained ultra-black powder product has an absorption rate of more than 99% for light with a wavelength of 180 nanometers to 3000 nanometers, among which the light absorption in the visible light region reaches 99.6%.
[0034] 2. The present invention uses a specific multi-element alloy component as a component of the monomer skeleton in the powder, which greatly improves the plasma frequency of the alloy, thereby making it have high absorption characteristics in a wider wavelength range, and can further improve the absorbance of the ultra-black powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is an electron microscope photograph of the multi-element alloy super black powder prepared in Example 1 of the present invention, with a magnification of 300X.
[0036] Figure 2 This is an electron microscope photo of a single particle of super black powder, with a magnification of 8000X. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0038] Part I Implementation of the Invention
[0039] The method for preparing the multi-element alloy ultra-black powder having a diatom frustule structure provided by the present invention comprises the following steps:
[0040] (1) According to the molar ratio of Ce:Co:Cu:La:Ni:Zn:Ag of 0.05:0.1:0.1:0.9:0.9:1.0:25, metal salts Ce(NO3)3, Co(NO3)2, Cu(NO3)2, La(NO3)3, Ni(NO3)2, Zn(NO3)2 and AgNO3 are taken as solutes; glycerol, sorbitol and deionized water are taken in a mass ratio of 1:1:4, mixed evenly and used as solvent; the solute is added to the solvent, the total mass ratio of the solute to the solvent is 30%, and the solution is obtained after stirring until it is completely dissolved; the purpose of this step is to dissolve the nitrate and form a uniform solution.
[0041] (2) According to the molar ratio of all metal salts: disodium ethylenediaminetetraacetate: sodium citrate being 1:1:2, disodium ethylenediaminetetraacetate and sodium citrate are added to solution one, and stirred until completely dissolved to obtain solution two; in this step, a metal ion complex is formed by adding disodium ethylenediaminetetraacetate and sodium citrate, and simultaneously coordinating the glycerol and sorbitol in step (1). The form of the complex allows the metal ions to be deposited at a uniform rate in the subsequent process without forming segregation.
[0042] (3) Add diatomaceous earth to solution 2 at a mass ratio of diatomaceous earth to solution 2 of 3:7, and continue stirring for 24 to 72 hours to obtain mixed solution 1; diatomaceous earth has a hierarchical porous structure, and the metal ion complex needs sufficient time to diffuse to the entire surface of the diatomaceous earth. Therefore, it is necessary to stir for a long time to allow the solution and diatomaceous earth to form sufficient infiltration.
[0043] (4) Adding the mixed solution 1 to a hydrothermal kettle with stirring, first start stirring for 10 to 20 minutes at a stirring rate of 300 rpm; after sealing the hydrothermal kettle, keep the temperature stepwise under stirring: first heat to 95° C. and keep warm for 1 to 3 hours; then heat to 185° C. and keep warm for 2 to 4 hours; then heat to 200° C. and keep warm for 10 to 12 hours; stop heating and cool to room temperature to obtain a mixed solution 1; in this step, the metal ion complex is formed and uniformly deposited on the surface of the diatomite through a stepwise heating hydrothermal process, and is further deposited and densified through hydrothermal nucleation at 95° C., hydrothermal deposition at 185° C., and hydrothermal deposition at 200° C.
[0044] (5) taking out the mixture 1, filtering it, washing it three times with deionized water, and drying it to obtain a powder 1;
[0045] (6) Powder 1 is added to a mixed solution containing KOH and CsOH; the concentration of the mixed solution is 2 mol / L, and the molar ratio of KOH to CsOH in the solution is 3:1; the temperature is raised to 65°C under a stirring rate of 300 rpm, and the temperature is kept for 8 to 12 hours; the heating is stopped and cooled to room temperature, filtered and washed three times with deionized water, and dried to obtain powder 2; in this step, the residual SiOx in the powder is removed by the mixed solution of KOH and CsOH.
[0046] (7) Repeat steps (1) and (2) to obtain solution 3; add powder 2 to solution 3 at a mass ratio of 2:8, and continue stirring for 10 to 30 minutes to obtain mixed solution 2;
[0047] (8) Add the second mixed solution into a hydrothermal reactor with stirring, start stirring for 10 to 20 minutes at a stirring rate of 300 rpm; after sealing the hydrothermal reactor, keep heating in a stepwise manner under stirring conditions: first heat to 110°C and keep warm for 1 to 3 hours; then heat to 165°C and keep warm for 2 to 4 hours; then heat to 220°C and keep warm for 10 to 12 hours; stop heating and cool to room temperature to obtain the second mixed solution; in this step, the densification of the deposition is further achieved by repeating the hydrothermal process, so that after the subsequent etching of SiOx, the voids left after etching are further filled, so that the strength of the microstructure is further improved to avoid collapse.
[0048] (9) taking out the mixture 2, filtering it, washing it three times with deionized water, and drying it to obtain a powder 3;
[0049] (10) adding powder 3 into a sodium borohydride aqueous solution with a mass percentage concentration of 25 wt%, heating to 65° C., and stirring continuously for 3 to 5 hours; cooling to room temperature, filtering, and washing three times with deionized water to obtain powder 4;
[0050] (11) placing the powder 4 in a tube furnace, introducing a mixture of 75% hydrogen and 25% nitrogen; heating to 750°C, and keeping the temperature for 10 to 12 hours; and cooling naturally to room temperature after the burning is completed to obtain a multi-component alloy powder with a diatom frustule structure. In this step, the diversified metal ion complex is reduced to a multi-component alloy component by burning in a reducing atmosphere, thereby forming a skeleton structure of a monomer particle.
[0051] Part II Examples and Comparative Examples
[0052] Embodiment 1:
[0053] A method for preparing a multi-element alloy ultra-black powder having a diatom frustule structure comprises the following steps:
[0054] (1) According to the molar ratio of Ce: Co: Cu: La: Ni: Zn: Ag being 0.05: 0.1: 0.1: 0.9: 0.9: 1.0: 25, Ce(NO3)3, Co(NO3)2, Cu(NO3)2, La(NO3)3, Ni(NO3)2, Zn(NO3)2, and AgNO3 were taken as solutes, added into a mixed solvent of glycerol: sorbitol: deionized water in a mass ratio of 1: 1: 4, the total mass ratio of the solute to the solvent being 30%, and stirred until completely dissolved to obtain solution 1;
[0055] (2) adding disodium ethylenediaminetetraacetate and sodium citrate to solution 1 in a molar ratio of total metal salts: disodium ethylenediaminetetraacetate: sodium citrate of 1:1:2, and stirring until completely dissolved to obtain solution 2;
[0056] (3) Add diatomaceous earth to solution 2 and continue stirring for 24 hours to obtain a mixed solution 1, wherein the mass ratio of diatomaceous earth to solution 2 is 3:7.
[0057] (4) adding the mixed solution 1 obtained in step (3) to a hydrothermal kettle with stirring, starting stirring, maintaining the stirring rate at 300 rpm, and stirring for 10 minutes; maintaining stirring, sealing the hydrothermal kettle, heating to 95° C., and keeping the temperature for 1 hour; then heating to 185° C., and keeping the temperature for 2 hours; then heating to 200° C., and keeping the temperature for 10 hours; after stopping heating, cooling to room temperature to obtain a mixture 1;
[0058] (5) taking the mixture obtained in step (4) out of the hydrothermal kettle, filtering and washing three times with deionized water, and drying to obtain a powdery substance;
[0059] (6) Powder 1 was added to a 2 mol / L KOH / CsOH aqueous solution, with a molar ratio of KOH to CsOH of 3:1, stirring was started, the stirring rate was maintained at 300 rpm, the temperature was raised to 65° C., the temperature was kept at this temperature for 8 hours, the heating was stopped, the powder was cooled to room temperature, filtered, washed three times with deionized water, and dried to obtain powder 2;
[0060] (7) Repeat the operations of steps (1) and (2) to obtain solution three; add the powder two obtained in step (6) to solution three, and continue stirring for 10 minutes to obtain mixed solution two, wherein the mass ratio of powder two to solution three is 2:8.
[0061] (8) Add the mixed solution 2 obtained in step (7) to a stirred hydrothermal kettle, start stirring, keep the stirring rate at 300 rpm, and stir for 10 minutes; keep stirring, seal the hydrothermal kettle, raise the temperature to 110° C., and keep it warm for 1 hour; then raise the temperature to 165° C., and keep it warm for 2 hours; then raise the temperature to 220° C., and keep it warm for 10 hours; stop heating, and cool to room temperature to obtain a mixed solution 2;
[0062] (9) The mixture obtained in step (8) is taken out from the hydrothermal reactor, filtered, washed three times with deionized water, and dried to obtain a powdery substance (3);
[0063] (10) dissolving sodium borohydride in deionized water to obtain a 25 wt % aqueous solution, adding the powder (3) obtained in step (9) to the aqueous solution of sodium borohydride, heating to 65° C., stirring continuously for 3 hours, cooling to room temperature, filtering and washing three times with deionized water to obtain powder (4);
[0064] (11) The powder obtained in step (10) is placed in a tube furnace, and a 75% hydrogen + 25% nitrogen mixture is introduced, the temperature is raised to 750° C., and the temperature is kept for 10 hours. After naturally cooling to room temperature, a multi-element alloy powder with a diatom frustule structure is obtained.
[0065] The powder was spread in a 2*2 square powder tank and tested for absorbance using a UV-visible-infrared spectrophotometer with an integrating sphere. The absorbance in the range of 180 nm to 3000 nm was 99.1% and in the visible light range was 99.6%.
[0066] Embodiment 2:
[0067] A method for preparing a multi-element alloy ultra-black powder having a diatom frustule structure comprises the following steps:
[0068] (1) According to the molar ratio of Ce: Co: Cu: La: Ni: Zn: Ag being 0.05: 0.1: 0.1: 0.9: 0.9: 1.0: 25, Ce(NO3)3, Co(NO3)2, Cu(NO3)2, La(NO3)3, Ni(NO3)2, Zn(NO3)2, and AgNO3 were taken as solutes, added into a mixed solvent of glycerol: sorbitol: deionized water in a mass ratio of 1: 1: 4, the total mass ratio of the solute to the solvent being 30%, and stirred until completely dissolved to obtain solution 1;
[0069] (2) adding disodium ethylenediaminetetraacetate and sodium citrate to solution 1 in a molar ratio of total metal salts: disodium ethylenediaminetetraacetate: sodium citrate of 1:1:2, and stirring until completely dissolved to obtain solution 2;
[0070] (3) Add diatomaceous earth to solution 2, and continue stirring for 72 hours to obtain a mixed solution 1, in which the mass ratio of diatomaceous earth to solution 2 is 3:7.
[0071] (4) adding the mixed solution 1 obtained in step (3) to a hydrothermal kettle with stirring, starting stirring, maintaining the stirring rate at 300 rpm, and stirring for 20 minutes; maintaining stirring, sealing the hydrothermal kettle, heating to 95° C., and keeping the temperature for 3 hours; then heating to 185° C., and keeping the temperature for 4 hours; then heating to 200° C., and keeping the temperature for 12 hours; after stopping heating, cooling to room temperature to obtain a mixture 1;
[0072] (5) taking the mixture obtained in step (4) out of the hydrothermal kettle, filtering and washing three times with deionized water, and drying to obtain a powdery substance;
[0073] (6) Powder 1 was added to a 2 mol / L KOH / CsOH aqueous solution, with a molar ratio of KOH to CsOH of 3:1, stirring was started, the stirring rate was maintained at 300 rpm, the temperature was raised to 65° C., the temperature was kept for 12 hours, the heating was stopped, the powder was cooled to room temperature, filtered and washed three times with deionized water, and dried to obtain powder 2;
[0074] (7) Repeat the operations of steps (1) and (2) to obtain solution three; add the powder two obtained in step (6) to solution three, and continue stirring for 30 minutes to obtain mixed solution two, wherein the mass ratio of powder two to solution three is 2:8.
[0075] (8) Add the mixed solution 2 obtained in step (7) to a stirred hydrothermal kettle, start stirring, keep the stirring rate at 300 rpm, and stir for 20 minutes; keep stirring, seal the hydrothermal kettle, raise the temperature to 110° C., and keep it warm for 3 hours; then raise the temperature to 165° C., and keep it warm for 4 hours; then raise the temperature to 220° C., and keep it warm for 12 hours; stop heating, and cool to room temperature to obtain a mixed solution 2;
[0076] (9) The mixture obtained in step (8) is taken out from the hydrothermal reactor, filtered, washed three times with deionized water, and dried to obtain a powdery substance (3);
[0077] (10) dissolving sodium borohydride in deionized water to obtain a 25 wt % aqueous solution, adding the powder (3) obtained in step (9) to the aqueous solution of sodium borohydride, heating to 65° C., stirring for 5 hours, cooling to room temperature, filtering and washing three times with deionized water to obtain powder (4);
[0078] (11) The powder obtained in step (10) is placed in a tube furnace, and a 75% hydrogen + 25% nitrogen mixture is introduced, the temperature is raised to 750° C., and the temperature is kept for 12 hours. After naturally cooling to room temperature, a multi-element alloy powder with a diatom frustule structure is obtained.
[0079] The powder was spread in a 2*2 square powder tank and the absorbance was tested by a UV-visible-infrared spectrophotometer with an integrating sphere. The absorbance in the range of 180 nm to 3000 nm was 99.4% and in the visible light range was 99.8%.
[0080] Embodiment 3:
[0081] A method for preparing a multi-element alloy ultra-black powder having a diatom frustule structure comprises the following steps:
[0082] (1) According to the molar ratio of Ce: Co: Cu: La: Ni: Zn: Ag being 0.05: 0.1: 0.1: 0.9: 0.9: 1.0: 25, Ce(NO3)3, Co(NO3)2, Cu(NO3)2, La(NO3)3, Ni(NO3)2, Zn(NO3)2, and AgNO3 were taken as solutes, added into a mixed solvent of glycerol: sorbitol: deionized water in a mass ratio of 1: 1: 4, the total mass ratio of the solute to the solvent being 30%, and stirred until completely dissolved to obtain solution 1;
[0083] (2) adding disodium ethylenediaminetetraacetate and sodium citrate to solution 1 in a molar ratio of total metal salts: disodium ethylenediaminetetraacetate: sodium citrate of 1:1:2, and stirring until completely dissolved to obtain solution 2;
[0084] (3) Add diatomaceous earth to solution 2, and continue stirring for 48 hours to obtain a mixed solution 1, in which the mass ratio of diatomaceous earth to solution 2 is 3:7.
[0085] (4) adding the mixed solution 1 obtained in step (3) to a hydrothermal kettle with stirring, starting stirring, maintaining the stirring rate at 300 rpm, and stirring for 15 minutes; maintaining stirring, sealing the hydrothermal kettle, heating to 95° C., and keeping the temperature for 2 hours; then heating to 185° C., and keeping the temperature for 3 hours; then heating to 200° C., and keeping the temperature for 11 hours; after stopping heating, cooling to room temperature to obtain a mixture 1;
[0086] (5) taking the mixture obtained in step (4) out of the hydrothermal kettle, filtering and washing three times with deionized water, and drying to obtain a powdery substance;
[0087] (6) Powder 1 was added to a 2 mol / L KOH / CsOH aqueous solution, with a molar ratio of KOH to CsOH of 3:1, stirring was started, the stirring rate was maintained at 300 rpm, the temperature was raised to 65° C., and the temperature was kept for 10 hours. The heating was stopped, the mixture was cooled to room temperature, filtered, washed three times with deionized water, and dried to obtain powder 2;
[0088] (7) Repeat the operations of steps (1) and (2) to obtain solution three; add the powder two obtained in step (6) to solution three, and continue stirring for 20 minutes to obtain mixed solution two, wherein the mass ratio of powder two to solution three is 2:8.
[0089] (8) Add the mixed solution 2 obtained in step (7) to a stirred hydrothermal kettle, start stirring, keep the stirring rate at 300 rpm, and stir for 15 minutes; keep stirring, seal the hydrothermal kettle, raise the temperature to 110° C., and keep it warm for 2 hours; then raise the temperature to 165° C., and keep it warm for 3 hours; then raise the temperature to 220° C., and keep it warm for 11 hours; stop heating, and cool to room temperature to obtain a mixed solution 2;
[0090] (9) The mixture obtained in step (8) is taken out from the hydrothermal reactor, filtered, washed three times with deionized water, and dried to obtain a powdery substance (3);
[0091] (10) dissolving sodium borohydride in deionized water to obtain a 25 wt % aqueous solution, adding the powder (3) obtained in step (9) to the aqueous solution of sodium borohydride, heating to 65° C., stirring continuously for 4 hours, cooling to room temperature, filtering and washing three times with deionized water to obtain powder (4);
[0092] (11) The powder obtained in step (10) is placed in a tube furnace, and a 75% hydrogen + 25% nitrogen mixture is introduced, the temperature is raised to 750° C., and the temperature is kept for 11 hours. After naturally cooling to room temperature, a multi-element alloy powder with a diatom frustule structure is obtained.
[0093] The powder was spread in a 2*2 square powder tank and tested for light absorption using a UV-visible-infrared spectrophotometer with an integrating sphere. The powder has a light absorption rate of 99.2% in the range of 180 nm to 3000 nm and a light absorption rate of 99.7% in the visible light range.
[0094] Comparative Example 1: Diatom frustule powder before modification
[0095] Take the diatomite used in Example 1, spread it in a 2*2 square powder tank, and test the light absorption by a UV-visible-infrared spectrophotometer with an integrating sphere. The light absorption of the diatomite in the range of 180 nm to 3000 nm is 20.2%, and the light absorption in the visible light range is 30.1%.
[0096] Comparative Example 2: Ultra-black powder of prior art
[0097] The product was prepared by referring to the scheme recorded in the open document CN 110952075 A to obtain ultra-black powder 1.
[0098] The powder was spread in a 2*2 square powder tank and tested for light absorption using a UV-visible-infrared spectrophotometer with an integrating sphere. The powder had a light absorption rate of 98.1% in the range of 180 nm to 3000 nm and a light absorption rate of 97.6% in the visible light range.
[0099] Comparative Example 3: Ultra-black powder II of the prior art
[0100] The product was prepared according to the scheme described in patent document CN 117024995 A to obtain ultra-black powder 2.
[0101] The powder was spread in a 2*2 square powder tank and tested for light absorption using a UV-visible-infrared spectrophotometer with an integrating sphere. The powder had a light absorption rate of 97.1% in the range of 180 nm to 3000 nm and a light absorption rate of 96.3% in the visible light range.
[0102] Comparative Example 4: Commercial super black powder
[0103] Purchase the commercially available super black powder product of model MA100.
[0104] The powder was spread in a 2*2 square powder tank and tested for light absorption using a UV-visible-infrared spectrophotometer with an integrating sphere. The powder had a light absorption rate of 91.8% in the range of 180 nm to 3000 nm and a light absorption rate of 93.2% in the visible light range.
[0105] Results analysis and summary
[0106] In Comparative Example 1, the diatom frustule powder before modification is mainly composed of amorphous silicon dioxide, and the light absorption of silicon dioxide as a material itself is very limited. Therefore, the light absorption gain brought by the diatom frustule structure is not enough to make the diatom frustule powder absorb light to a higher level.
[0107] The super black powder 1 in Comparative Example 2 has a simple core-shell structure, so its product performance cannot be compared with that of the powder with a diatom frustule structure; the super black powder 2 in Comparative Example 3 has a relatively simple loading structure, and its product light absorption performance cannot be compared with that of the powder with a diatom frustule structure; the commercial super black powder product in Comparative Example 3 has a low absorbance, which not only fails to reach the level of the present invention, but is also lower than the super black powders in Comparative Examples 2 and 3.
[0108] From the above comparison, it can be seen that the ultra-black powder product of the present invention has the excellent performance of ultra-high light absorption rate compared with these prior arts.
[0109] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a multi-element alloy ultra-black powder having a diatom frustule structure, characterized in that: The following steps are involved: (1) According to the molar ratio of Ce: Co: Cu: La: Ni: Zn: Ag being 0.05: 0.1: 0.1: 0.9: 0.9: 1.0: 25, the corresponding metal salt is taken as the solute; glycerol, sorbitol, and deionized water are taken at a mass ratio of 1: 1: 4, mixed evenly, and used as the solvent; the solute is added to the solvent, stirred until completely dissolved to obtain a solution 1; (2) adding disodium ethylenediaminetetraacetate and sodium citrate to solution 1 in a molar ratio of total metal salts: disodium ethylenediaminetetraacetate: sodium citrate of 1:1:2, and stirring until completely dissolved to obtain solution 2; (3) adding diatomaceous earth to solution 2 at a mass ratio of diatomaceous earth to solution 2 of 3:7, and continuously stirring for 24 to 72 hours to obtain a mixed solution 1; (4) adding the mixed solution 1 to a hydrothermal kettle with stirring, and starting stirring first; after sealing the hydrothermal kettle, stepwise heating to 200° C. under stirring, and keeping the temperature for 10 to 12 hours; stopping heating and cooling to room temperature to obtain a mixed solution 1; (5) taking out the mixture 1, filtering it, washing it with deionized water, and drying it to obtain a powder 1; (6) adding powder 1 to a mixed solution containing KOH and CsOH; heating to 65° C. under stirring conditions, and keeping the temperature for 8 to 12 hours; stopping heating and cooling to room temperature, filtering and washing with deionized water, and drying to obtain powder 2; (7) Repeat steps (1) and (2) to obtain solution 3; add powder 2 to solution 3 at a mass ratio of 2:8, and continue stirring for 10 to 30 minutes to obtain mixed solution 2; (8) Adding the second mixed solution into a hydrothermal kettle with stirring, and starting stirring first; after sealing the hydrothermal kettle, stepwise heating to 220° C. under stirring, and keeping the temperature for 10 to 12 hours; stopping heating and cooling to room temperature to obtain the second mixed solution; (9) taking out the mixture 2, filtering it, washing it with deionized water, and drying it to obtain a powder 3; (10) adding powder 3 into a sodium borohydride aqueous solution, heating to 65° C., and stirring continuously for 3 to 5 hours; cooling to room temperature, filtering, and washing with deionized water to obtain powder 4; (11) The powder is placed in a tube furnace, and a mixture of 75% hydrogen and 25% nitrogen is introduced. After burning, the powder is naturally cooled to room temperature to obtain a multi-element alloy powder with a diatom frustule structure.
2. The method according to claim 1, characterized in that: In the step (1), the metal salt is Ce(NO3)3, Co(NO3)2, Cu(NO3)2, La(NO3)3, Ni(NO3)2, Zn(NO3)2 and AgNO3.
3. The method according to claim 1, characterized in that In the step (1), the mass ratio of the total mass of the solute to the mass of the solvent is 30%.
4. The method according to claim 1, characterized in that: In the step (4), the mixed solution is stirred for 10 to 20 minutes at a stirring rate of 300 rpm before the hydrothermal kettle is sealed; after the hydrothermal kettle is sealed, the stirring condition is maintained; the temperature is first raised to 95° C. and kept warm for 1 to 3 hours; then the temperature is raised to 185° C. and kept warm for 2 to 4 hours; and then the temperature is raised to 200° C. and kept warm for 10 to 12 hours.
5. The method according to claim 1, characterized in that In the steps (5), (6), (9) and (10), the filtrate is filtered and then washed three times with deionized water.
6. The method according to claim 1, characterized in that In the step (6), the concentration of the mixed solution of KOH and CsOH is 2 mol / L, the molar ratio of KOH to CsOH in the solution is 3:1; and the stirring rate is 300 rpm.
7. The method according to claim 1, characterized in that In the step (8), before the hydrothermal kettle is sealed, the mixed solution 2 is stirred for 10 to 20 minutes at a stirring rate of 300 rpm; after the hydrothermal kettle is sealed, the stirring condition is maintained; the temperature is first raised to 110° C. and kept warm for 1 to 3 hours; then the temperature is raised to 165° C. and kept warm for 2 to 4 hours; and then the temperature is raised to 220° C. and kept warm for 10 to 12 hours.
8. The method according to claim 1, characterized in that: In the step (10), the mass percentage concentration of the sodium borohydride aqueous solution is 25 wt %.
9. The method according to claim 1, characterized in that: In the step (11), the calcination refers to heating the powder to 750° C. and keeping the temperature for 10 to 12 hours.
Citation Information
Patent Citations
Core-shell-type ultra black powder material and preparation method thereof
CN110952075A
Super-black light-absorbing powder and preparation method and application thereof
CN117024995A